Inside the world of non-suicidal self-injury e-communities: Language, identity and need for belonging - Vinay Jagdish Sukhija; Elisa Mancinelli; Rachele Del Guerra; Silvia Salcuni (PLoS ONE, 2025)
Non-suicidal self-injury e-Communities are increasingly gaining popularity, and people who self-harm are turning to these groups to share their experiences and feelings. They are doing so through a unique set of specific slang words related to the behaviour of self-harm that seems to be pertinent to these e-communities. In this regard, this study aims to explore slang words and differences in their usage across communities. A sample of 410 posts and respective comments were extracted from two self-harm e-communities on Reddit based on predetermined slang keywords through Python Reddit API Wrapper. A content analysis was performed, indicating that slang words prevailed across 8 different domains; the 3 most prevalent were sense of belonging, medical care, and sarcasm and self-deprecation. Inter-rater reliability of the analysis found strong agreement across the 3 individual coders. Chi-square analyses were then performed to evaluate differences in the frequency of domains and subdomains between the two self-harm e-communities. Significant differences were observed across subdomains (X 2 = 244.9, p = 0.001) but not across the domains. Finally, sentiment analysis was conducted, and Mann-Whitney U-tests across the two communities found that one of the two is significantly more negative in sentiment value (U = 23808, p = 0.019) while, consequently, the other had a significantly larger overall compound sentiment score (U = 17429, p = 0.003) . Overall, lived experience findings from the textual descriptions of users indicate the pervasiveness of slang words across these communities and the further need to investigate their nuanced and varied usage. Building on the person-centred framework in NSSI research, a case is made for the development of more targeted and tailored interventions, such as e-health mobile and application-based interventions, that consider the unique contributions of NSSI e-Communities in the life and context of a person who engages in self-harm.